A molten glass wall. Analysis of tactical use of female fragility imaginary: The case of Jamia Hafsa female militia (2014)
Departing from the post-colonial theoretical approaches exposed by Chandra Talpade Mohanty and Frantz Fanon, this article presents an analysis on the tactics and strategies used by the Syeda Jamian Hafsa female students. The way in which the Jihadists turn the traditional imaginary around female vulnerability into a tactical attack instrument is analyzed.